Fact-finding study of the All Japan Judo Kata Championship - Kiryu, S.; Otsuji, H. (Association for the Scientific Studies on Judo, Kodokan, 2023)
This Study reviewed the literature to elucidate the development of kata competitions in Japan, with the aim of obtaining basic knowledge to be applied in the future dissemination of kata instruction. Information was extracted from articles and other documents related to the All Japan Judo Kata Championship. The following information was clarified.